External validity of a cardiovascular screening including a coronary artery calcium examination in middle-aged individuals from the general population. (July 2018) - Grønhøj, Mette H; Gerke, Oke; Mickley, Hans; Steffensen, Flemming H; Lambrechtsen, Jess; Sand, Niels Peter R; Rasmussen, Lars M; Olsen, Michael H; Hallas, Jesper; Diederichsen, Axel CP
Background: Coronary artery calcium is important in cardiovascular risk stratification, but this knowledge is based on studies with a significant selection bias. This study aims to evaluate the external validity of a screening programme including coronary artery calcium examination, and the association between coronary artery calcium and cardiovascular events. Design: Multi-centre population based study. Methods: Randomly selected middle-aged men and women ( N  = 1751) free of cardiovascular disease were invited to the examination during 2009–2010. Participation rate in the examination was 70%. Participants ( n  = 1227) and non-participants ( n  = 524) were compared regarding: cardiovascular medical treatment, Charlson comorbidity index and socioeconomic status (evaluated by cohabitation, gross income and education). Study endpoints were cardiovascular events and mortality. Results: Non-participants had a significant higher comorbidity ( p  = 0.003) and a lower socioeconomic status ( p  < 0.0001), while cardiovascular medical treatment was alike. Over a median follow-up time of 6.5 years the cardiovascular event and mortality rates were equal (6.7% vs . 6.4%, p  = 0.80 and 0.4% vs . 0.5%, p  = 0.76, respectively). Adjusted hazard ratio was 0.90 (95% confidence interval (CI) 0.63–1.37). Among participants, the extent of coronary artery calcium was significantly associated with increased risk of cardiovascular events (hazard ratio 1.92, 95% CI 1.03–3.54, hazard ratio 3.66, 95% CI 1.82–7.32, hazard ratio 6.51, 95% CI 3.17–13.36 for coronary artery calcium scores 1–99, 100–399, ≥400 AU, respectively). Conclusions: Non-participants had a higher comorbidity index and a lower socioeconomic status, but the cardiovascular event and mortality rates were equal to those of participants. Thus, a screening programme including a coronary artery calcium examination had a high external validity regarding cardiovascular risk, but also a significant social imbalance.